Green synthesis of iron nanoparticles using aqueous extract of Turbinaria conoides (J. Agardh) and their anticancer properties - Bensy, Asha D. V.; Christobel, G. Johnsi (Current Botany, 2021)
Marine macroalgae produce numerous bioactive compounds with potential pharmacological properties. In this study, macroalga was collected from the Gulf of Mannar, India and identified as, Turbinaria conoides (J. Agardh). The aqueous extract of T. conoides was used to synthesize iron nanoparticles (NPs). The synthesized iron NPs were characterized by X –ray diffraction analysis, Scanning Electron Microscopy, and Transmission Electron Microscopy. The synthesized NPs showed potent activity against DLD1 and HeLa cell lines.